Maria Kalaw Katigbak a charmed life - Mercado, Monina A. (Monina Allarey) (Pasig City Anvil, 2007)
"...the moment [Maria] took the spotlight as senator-elect in a clean Liberal Party sweep with President Diosdado Macapagal, we always knew that one day a Maria Kalaw Katigbak biography had to be written. It is one of those inevitable fruitions of a life laden with a noble genealogy, beauty, intellectual prowess, and a charmed destiny." - Puri K. Katigbak, Prologue.
Prologue : investing in memories / by Puri K. Katigbak -- 1. 1911 -- 2. A childhood in Lipa -- 3. The making of a humanist -- 4. Pura -- 5. "Heart of my heart" -- 6. Life with Pura and Teodoro -- 7. Bringing up Maria -- 8. "Miss Self-Control" -- 9. A historical imperative -- 10. "All head, all heart" -- 11. A deluge of memories -- 12. Pepito -- 13. Maria becomes Mrs. Katigbak -- 14. Maria's young family -- 15. Raising daughters -- 16. Maria's only son -- 17. Why Maria loved girl scouting -- 18. Taking charge of the Girl Scouts -- 19. Maria runs for the Senate -- 20. Tuition on the campaign trail -- 21. The Senate novice -- 22. Truth in lending -- 23. To Paris--and back -- 24. Immersed in the Senate -- 25. Writing a law for culture -- 26. The religious instruction bill -- 27. Maria lifts the bamboo curtain -- 28. Eight days in Beijing -- 29. In sum : the China visit -- 30. The Vietnam mission -- 31. Maria in Las Vegas, the UN, and the Fair Lane -- 32. Maria and the Blairs -- 33. Notice of ouster -- 34. "But who is not guilty?" -- 35. Unseated by a dead law? -- 36. Allow me to continue -- 37. Running again -- 38. Results and post mortem -- 39. Writing a column -- 40. The Lipa rest house -- 41. Maria as a writer -- 42. Maria gets into the movies -- 43. Maria as grandmother -- 44. 1992 -- 45. Sudden loss -- 46. Maria's pall of silence -- 47. Maria dies -- 48. Maria's wake and burial -- 49. Epilogue : timing / by Maria Kalaw Katigbak.
Fi-9608r donated by Marinela Katigbak-Fabella
Keywords: Katigbak, Maria Kalaw -- 1911-1992.; Women politicians -- Philippines -- Biography; Legislators -- Philippines -- Biography; Philippines -- Biography